Investigation of the Barriers Influence in the Air Gap Point-Plane by Electric Field Estimation - ROUINI Abdelghani; MAHI Djilali; LARBI Messaouda (Universty Of El-oued جامعة الوادي, 2019)
—In this paper ,we develop a model for three computation of the electric field in the presence of a space charge which is given in its turn after the knowledge of the effective ionization factor. The effect of the barriers in the intervals of air point-plan was the subject of several investigations; those showed that the influence of the barrier is especially related to the accumulation of loads on its surface on the active electrode side. Thus the barrier constitutes a mechanical and electrostatic obstacle with the increase in discharge. From an economic standpoint, the quality and dimensions of the barrier should not be the only criteria for the insulation coordination, in each system of HV electrodes. Results show that electric stress in the air gap decreases due to space charge left in the point-barrier gap, but it increases suddenly at the handle of the avalanches and on the upper barrier surface. This later effect related to the presence of the dielectric barrier is due to the polarization charge.
Intervention
Keywords: Streamer; Electric field; Space Charge Barrier; Ionization Factors; Point-Plane; FVM